2007
DOI: 10.1177/154193120705101902
|View full text |Cite
|
Sign up to set email alerts
|

Detection-Action Linkage in Vigilance: Effects on Workload and Stress

Abstract: Using a simulated UAV control task in which a vigilance display warned observers of the presence of enemy threats, Gunn et al. (2005) reported that perceived mental workload in relation to the vigilance task was unexpectedly low. The present study did not confirm that finding. It did show, however, that vigilance performance was greater and task induced stress was less among observers who had the opportunity to act upon vigilance signal detections by destroying the enemy threats than among those who detected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…It may reflect the greater interest and challenge provided by working on a complex, gamelike task. Parsons, Warm, Nelson, Riley, and Matthews (2007) showed that increasing the operator's level of control over task events increases task engagement. Thus, synthetic task environments may have advantages over simple laboratory tasks as a methodology for investigating stress responses elicited by complex operational tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It may reflect the greater interest and challenge provided by working on a complex, gamelike task. Parsons, Warm, Nelson, Riley, and Matthews (2007) showed that increasing the operator's level of control over task events increases task engagement. Thus, synthetic task environments may have advantages over simple laboratory tasks as a methodology for investigating stress responses elicited by complex operational tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also prevented from controlling the direction of movement, and they could not pan their viewpoint to any direction other than that preset. They were thus prevented from actively exploring the environment, which itself can influence observer' response (Gunn et al 2005;Parsons 2007). …”
Section: Stimulus Background and Observer 'Movement'mentioning
confidence: 99%
“…Allowing some scope for personal configuration of the system may be valuable. Parsons et al (2007) compared two versions of a vigilance task, presented in a military context. Participants were required either to simply register detection of symbols representing enemy missile launchers or to additionally acquire and destroy the target using a mouse response, following detection.…”
Section: Applicationsmentioning
confidence: 99%